1999
DOI: 10.1046/j.1365-2648.1999.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study into the perceptions of caring and nursing among student nurses

Abstract: A longitudinal study of a cohort of student nurses was undertaken in order to investigate whether changes in perceptions of nursing and caring take place and how perceptions of nursing and caring are related. The Caring Dimensions Inventory (CDI) and the Nursing Dimensions Inventory (NDI) were employed for data collection at entry to nurse education and after 12 months. There were significant changes in the scores of a range of items in both inventories which suggested that student nurses lose some of their id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 10 publications
0
32
0
4
Order By: Relevance
“…The same result was also found by Mackintosh (), where a significant loss of idealism about care within nursing was noted as the nursing program proceeded. According to Watson, Deary, and Lea (), this may indicate negative development as a result of the educational and clinical processes, or it may even indicate burnout. This result is surprising considering that students' caring behaviors are expected to grow during the course of nursing education and training as a result of mastery, experience, knowledge, and skills on nursing (Benner, ; Eklund‐Myrskog, ), and these to continue to develop in their role in the nursing profession (Alpers, Jarrell, & Wotring, ).…”
Section: Discussionmentioning
confidence: 99%
“…The same result was also found by Mackintosh (), where a significant loss of idealism about care within nursing was noted as the nursing program proceeded. According to Watson, Deary, and Lea (), this may indicate negative development as a result of the educational and clinical processes, or it may even indicate burnout. This result is surprising considering that students' caring behaviors are expected to grow during the course of nursing education and training as a result of mastery, experience, knowledge, and skills on nursing (Benner, ; Eklund‐Myrskog, ), and these to continue to develop in their role in the nursing profession (Alpers, Jarrell, & Wotring, ).…”
Section: Discussionmentioning
confidence: 99%
“…While my study does not provide longitudinal data, there are two substantive issues worth noting with regards to findings in the nursing literature. On the one hand, it is clear that caring never quite disappears from the discursive repertoire of nursing students; if anything it becomes more salient as they move through their educational experience, as indicated by the findings of Watson et al (1999) about the convergence of "nursing" and "caring" (i.e. the two become synonyms).…”
Section: Educated Caring: the Challenge Of Integrating Science And Camentioning
confidence: 94%
“…For example, in a longitudinal study of nursing students' perceptions of caring, Watson et al (1999) found that students lose "idealism about nursing and caring after 12 months in nurse education" (p. 1228). The authors argue that this is a "negative development...and could even indicate burnout" (p. 1235).…”
Section: Educated Caring: the Challenge Of Integrating Science And Camentioning
confidence: 96%
“…Signifi cant for selection of occupation are role models in the family, among friends, as well as positive experiences with nurses 7,[9][10][11][12] . Previous positive experience when caring for the sick, and insuffi cient knowledge of the nursing profession often cause idealistic perception of nursing, which can cause stress and discomfort during the study due to a confl ict between the ideal image of nursing and nursing what it really is 9,13,14 . Th e aim of this study was to determine the attitudes of nursing students towards nursing, and changes in their attitudes during the study.…”
Section: Introductionmentioning
confidence: 99%